2004
DOI: 10.1016/j.ymthe.2004.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic HER2/Neu DNA Vaccine Inhibits Mouse Tumor Naturally Overexpressing Endogenous Neu

Abstract: The therapeutic efficacy of HER2/c-erbB-2/neu DNA immunization on mouse tumor cells expressing exogenous human or rat p185neu but not on mouse tumor cells naturally expressing mouse p185neu has been demonstrated. We investigated the feasibility of using N-terminal rat neu DNA immunization on mouse tumor overexpressing endogenous p185neu and enhancing the therapeutic efficacy of this vaccine by fusion to various cytokine genes, including interleukin-2 (IL-2), interleukin-4 (IL-4), or granulocyte-macrophage colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 52 publications
2
68
0
3
Order By: Relevance
“…36 We have also shown that the combination of CD4 + T-cell depletion and intramuscular injection of the hN'-neu DNA vaccine causes dramatic increases in CD8 + T-cell responses and antitumor effects in a MBT-2 tumor model. 22 We propose that both CD8 + T cells and conventional CD4 + T-helper cells may contribute to the antitumor immunity against HER-2/neu-expressing tumors effected by the HER-2/neu DNA vaccine delivered by a gene gun. Moreover, this notion suggests that the removal of CD4 + Treg lymphocytes may further increase the effectiveness of hN'-neu DNA vaccination.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…36 We have also shown that the combination of CD4 + T-cell depletion and intramuscular injection of the hN'-neu DNA vaccine causes dramatic increases in CD8 + T-cell responses and antitumor effects in a MBT-2 tumor model. 22 We propose that both CD8 + T cells and conventional CD4 + T-helper cells may contribute to the antitumor immunity against HER-2/neu-expressing tumors effected by the HER-2/neu DNA vaccine delivered by a gene gun. Moreover, this notion suggests that the removal of CD4 + Treg lymphocytes may further increase the effectiveness of hN'-neu DNA vaccination.…”
Section: Discussionmentioning
confidence: 98%
“…45 We further observed the surface expression of p185neu and major histocompatibility complex class I molecules on MBT-2 cells using flow cytometry. 22 Plasmid construction and preparation of the DNA vaccine A shRNA was constructed within a pHsU6 vector as described previously. 46 The targets were 5¢-GCAGCCGTGCCTTGTCAAA-3¢ÿ (for mouse Foxo3 shRNA) and 5¢-GCCGACCCGGTGTACTATA-3¢ÿ (for scramble shRNA).…”
Section: Mice and Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations